Recent Trends in Cancer Incidence: Impact of Risk Factors, Diagnostic Activities and Data Quality of Registration. Issue 4 (July 2014) - Dehler, Silvia; Tonev, Simeon; Korol, Dimitri; Rohrmann, Sabine; Dimitrova, Nadya
Aims and Background: Cancer incidence variations are influenced by different factors including socioeconomic status, risk factors and use of screening. The purpose of this study was to examine trends in cancer incidence in two urban areas in Europe showing differences in influencing factors but also some common characteristics in the context of data quality of the corresponding cancer registries. Methods: Age-standardized incidence rates (world standard – ASRW) for cases diagnosed in 2000–2009 for Sofia (Bulgaria) and the Canton of Zurich (Switzerland) were calculated using data from the corresponding cancer registries. Average annual percent change (AAPC) was estimated with Joinpoint regression analysis. Data quality was estimated in terms of proportions of microscopically verified (MV%) and deathcertificate-only (DCO%) cases. Results: ASRWs for all sites were higher in Zurich for men (311 vs 262 per 100, 000) and women (241 vs 231 per 100, 000) than in Sofia. Colorectal (both sexes), lung (men), cervical and corpus uteri cancer had a higher incidence in Sofia. Prostate, breast and lung (women) cancer were more often diagnosed in Zurich. A significant increase in female lung cancer incidence was observed in both areas. Overall incidence decreased in Zurich, while it did not significantly change in Sofia. MV% was lower in Sofia than in the Canton of Zurich but increased steadily up to 85% in 2009, whereas in the Canton of Zurich MV% was more or less stable around 95%. The DCO% of Sofia was 19% in 2000 and steadily decreased to 8% in 2009. In the Canton of Zurich, the DCO% decreased from 5% in 2000 but increased again from 2006 onwards, up to 3% in 2009. Conclusions: Cancer incidence rates differ between Sofia and Zurich. Differences concerning socioeconomic status, risk factors, use of cancer screening but also data quality may influence these results.